The Supererogatory and How Not To Accommodate It: A Reply to Dorsey. Issue 2 (22nd July 2015) - ARCHER, ALFRED
Abstract : It is plausible to think that there exist acts of supererogation (acts that are morally optional and morally better than the minimum that morality demands). It also seems plausible that there is a close connection between what we are morally required to do and what it would be morally good to do. Despite being independently plausible these two claims are hard to reconcile. My aim in this article will be to respond to a recent solution to this puzzle proposed by Dale Dorsey. Dorsey's solution to this problem is to posit a new account of supererogation. I will argue that Dorsey's account fails to succeed in achieving what an account of supererogation is supposed to achieve.